Parlamenti di guerra (1914-1945): Caso italiano e contesto europeo Parliaments at war (1914-1945): Italy and the European Context - Marco Meriggi (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2017)
During the First World War, the parliaments of the states involved in the conflict were, in most cases, forced to drastically limit their activity and were often precluded the possibility of fully exercising their prerogatives. More generally the spaces of freedom granted to the citizens, of which the parliamentary institution was the brightest symbol, shrank dramatically. At the same time, the power of military commands expanded, not only in trenches and on battlefields, but also in many areas of civilian life. However, in the final years of the war, the Parliaments succeeded not only in gradually regaining control, but also in pushing for an extension of their functions, initiating a process that in many states coincided with the transition from a liberal order to a full democratic order. The years of the "long" postwar period were however dense with contradictions. Legislative and executive law often grew together, while in some cases the imperative logic imposed for a long time in wartime re-emerged and consolidated. This volume, which examines several national cases, illustrates some of the ambivalent features of this dramatic phase of European history.